English Students' Ability in Using Lexical Collocations Viewed in Their Speaking Performances: A Case at English Department FBS UNP - Annike Putri Ardi; Hermawati Syarif; Ratmanida Ratmanida (Journal of English Language Teaching, 2018)
AbstractThis research was a descriptive quantitavie research about English students’ ability in using lexical collocations viewed intheirspeaking performances. The uses of lexical collocations has been concerned as the 2013 batch English students had been practicing English at classes they had taken and at schools they had taught their temporary students. Lexical collocations indicated natural English which knowledge of it is necessary to gain as they are going to teach their students in the future. 18 students who had done PLK activity were involved in speaking test and interviews. The lexical collocations found in students sentences were analyzed and the types were classified to see the correct uses or collocation problems. It was found that the students’ ability in using lexical collocations was poor. All types of lexical collocations were used with different proportions with Verb and adjective and Adjective and Noun as the most frequent types of lexical collocations used. The problems were frequently of Verb and Noun and Adjective and Noun types. The causes of the problems were the limited knowledge of lexical collocations, the ignorance of the use of lexical collocations, and the use of direct translation from L1 to L2. It is concluded the more lexical collocations used, the more possible problems to occur.